1991
DOI: 10.1029/91wr00241
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale natural gradient tracer test in sand and gravel, Cape Cod, Massachusetts: 1. Experimental design and observed tracer movement

Abstract: A large‐scale natural gradient tracer experiment was conducted on Cape Cod, Massachusetts, to examine the transport and dispersion of solutes in a sand and gravel aquifer. The nonreactive tracer, bromide, and the reactive tracers, lithium and molybdate, were injected as a pulse in July 1985 and monitored in three dimensions as they moved as far as 280 m down‐gradient through an array of multilevel samplers. The bromide cloud moved horizontally at a rate of 0.42 m per day. It also moved downward about 4 m becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
185
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(194 citation statements)
references
References 23 publications
7
185
0
2
Order By: Relevance
“…The configuration mostly studied in the past is that of uniform flows in the average (a situation which is ascribed to natural gradient conditions). Mean uniform flows have been investigated experimentally by controlled field tests (e.g., Sudicky 1986; LeBlanc et al 1991), and theoretically by means of numerical codes (a wide review can be found in Zhang 2002;Rubin 2003), as well as of analytical tools (Dagan 1989). There are however many hydrological applications (such as protection zones of wells, pump and treat remediation procedures, pumping tests analysis) of non uniform mean flows.…”
Section: Introductionmentioning
confidence: 99%
“…The configuration mostly studied in the past is that of uniform flows in the average (a situation which is ascribed to natural gradient conditions). Mean uniform flows have been investigated experimentally by controlled field tests (e.g., Sudicky 1986; LeBlanc et al 1991), and theoretically by means of numerical codes (a wide review can be found in Zhang 2002;Rubin 2003), as well as of analytical tools (Dagan 1989). There are however many hydrological applications (such as protection zones of wells, pump and treat remediation procedures, pumping tests analysis) of non uniform mean flows.…”
Section: Introductionmentioning
confidence: 99%
“…Tracer tests can be conducted in steady state or transient mode. Injection of one or more tracers at a time is possible [6][7][8][9][10][11]. Interpretation of tracer test can be numerical and analytical, but the analytical analysis is restricted to steady state flow while numerical analysis can deal with steady or transient state flow.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we limit the analysis to plumes that exist over scales captured in the first three hierarchical levels, which would include the overall scale of some of the better known natural-gradient tracer tests, e.g. Borden (Sudicky, 1986) and Cape Cod (Leblanc et al, 1991).…”
Section: Sedimentary Architecturementioning
confidence: 99%